Fiber tract‐specific white matter lesion severity Findings in late‐life depression and by AGTR1 A1166C genotype. Issue 2 (22nd October 2011) - Taylor, Warren D.; Zhao, Zheen; Ashley‐Koch, Allison; Payne, Martha E.; Steffens, David C.; Krishnan, Ranga R.; Hauser, Elizabeth; MacFall, James R.
Abstract Past work demonstrated that late‐life depression is associated with greater severity of ischemic cerebral hyperintense white matter lesions, particularly frontal lesions. However, these lesions are also associated with other neuropsychiatric deficits, so these clinical relationships may depend on which fiber tracts are damaged. We examined the ratio of lesion to nonlesioned white matter tissue within multiple fiber tracts between depressed and nondepressed elders. We also sought to determine if the AGTR1 A1166C and BDNF Val66Met polymorphisms contributed to vulnerability to lesion development in discrete tracts. The 3T structural MR images and blood samples for genetic analyses were acquired on 54 depressed and 37 nondepressed elders. Lesion maps were created through an automated tissue segmentation process and applied to a probabilistic white matter fiber tract atlas allowing for identification of the fraction of the tract occupied by lesion. The depressed cohort exhibited a significantly greater lesion ratio only in the left upper cingulum near the cingulate gyrus (F(1, 86) = 4.62, P = 0.0344), supporting past work implicating cingulate dysfunction in the pathogenesis of depression. In the 62 Caucasian subjects with genetic data, AGTR1 C1166 carriers exhibited greater lesion ratios across multiple tracts including the anterior thalamic radiation and inferior fronto‐occipital fasciculus. In contrast, BDNF Met allele carriers exhibited greater lesion ratios only in the frontal corpus callosum. Although these findings did not survive correction for multiple comparisons, this study supports our hypothesis and provides preliminary evidence that genetic differences related to vascular disease may increase lesion vulnerability differentially across fiber tracts. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.